E. Aubert de la Rue, L ' homme et les volcans, Paris, Gallimard (Col. Deffontaines), 1958, 381 p. - M. Z. (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Geografía, 1960)

(untitled)
Fil: M. Z.. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras